1995
DOI: 10.1002/eji.1830250833
|View full text |Cite
|
Sign up to set email alerts
|

Experimental gene therapy of cancer using tumor cells engineered to secrete interleukin‐13

Abstract: Cytokines locally delivered to the site of a tumor boost both specific and nonspecific host anti-tumor defenses. Interleukin (IL)-13 is a recently described cytokine produced by mouse type 2 helper T lymphocytes. The aim of this study was to evaluate the inhibition of tumor growth induced by IL-13 delivered locally within or around transplanted tumor cells in mice. We observed that local administration of IL-13 at the site of transplanted tumor cells in vivo had potent inhibitory effects on growth of both immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…The leukocyte infiltrate of IL-13-secreting tumors has a major mononuclear phagocyte component (75). It is tempting to speculate that IL-13 might act directly in the recruitment of monocytes for its chemotactic activity (76), or by inducing the expression of IL-8 receptors on these effector cells.…”
Section: Discussionmentioning
confidence: 99%
“…The leukocyte infiltrate of IL-13-secreting tumors has a major mononuclear phagocyte component (75). It is tempting to speculate that IL-13 might act directly in the recruitment of monocytes for its chemotactic activity (76), or by inducing the expression of IL-8 receptors on these effector cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with genetically modified tumor cells have highlighted the participation of several types of cells, including neutrophils, eosinophils, mast cells, lymphocytes, and NK cells in tumor rejection (15)(16)(17)(18)(19)(20). To determine the relative roles of lymphocytes in the rejection of IL-21-transduced tumor cells, equal numbers (10 5 ) of B16F1-IL-21 or control B16F1-GFP cells were injected into T and B cell-deficient (SCID) mice.…”
Section: Il-21 Requires Both Innate and Adaptive Immunity In Tumor Rementioning
confidence: 99%
“…IL-13 also mediates biological activities in tumor cells. [7][8][9] We have shown that the receptor for IL-13 (IL-13R) in tumor cells exists as two different types. [10][11][12][13][14][15] Type I IL-13R consists of IL-13Ra2 (also known as IL-13Ra), IL-13Ra1 (also known as IL-13Ra 0 ), and IL-4Ra (also known as IL-4Rb) chains, while type II IL-13R consists of IL-13Ra1 and IL-4Ra chains.…”
Section: Introductionmentioning
confidence: 99%